2016
DOI: 10.1007/s00438-016-1226-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the expansin gene family in tobacco (Nicotiana tabacum)

Abstract: Expansins are pH-dependent cell wall loosening proteins which form a large family in plants. They have been shown to be involved in various developmental processes and been implicated in enabling plants' ability to absorb nutrients from the soil as well as conferring biotic and abiotic stress resistances. It is therefore clear that they can be potential targets in genetic engineering for crop improvement. Tobacco (Nicotiana tabacum) is a major crop species as well as a model organism. Considering that only a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 57 publications
16
55
0
Order By: Relevance
“…Many common light-responsive elements were identified between the 3 promoters as previously observed in tobacco expansin promoters. 22 The high occurrence of these motifs (40/33/26) is consistent with the high transcript levels of the 3 genes in response to light treatment ( Fig. 2A).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Many common light-responsive elements were identified between the 3 promoters as previously observed in tobacco expansin promoters. 22 The high occurrence of these motifs (40/33/26) is consistent with the high transcript levels of the 3 genes in response to light treatment ( Fig. 2A).…”
supporting
confidence: 80%
“…The opposite situation was reported for tobacco and strawberry expansin promoters. 22,24 Additionally, the promoter regions of expression genes in response to CK treatment in darkness (Fig. 2B).…”
mentioning
confidence: 99%
“…The majority of the EXPA members (82%) had three exons, while EXLB genes presented the largest number of exons, ranging from four to six, similar to Malus x Domestica and G. max (Zhang et al 2014b; Zhu et al 2014). The EXLA members had the same gene structure (4-exon/3-intron) in both Arachis species which differs from the usual 5-exon/4-intron EXLA structure of other plants (Ding et al 2016; Krishnamurthy et al 2014; Sampedro et al 2005). …”
Section: Resultsmentioning
confidence: 93%
“…Cell elongation is controlled by cell extensibility, which is regulated by cell wall-loosening proteins and enzymes, including expansin and xyloglucan endotransglycosylase (XET) [31]. It was reported that EXPA4 was highly expressed in germinating seeds and that EXPA3 was highly expressed in young roots and germinating seeds in tobacco [32].…”
Section: Expression Of Expansin Genesmentioning
confidence: 99%